Do Research Leaders at a Brazilian University Legitimize Their Institutional Policy for Innovation? - Tonelli, Dany Flávio; Oliveira, Vânia Aparecida Rezende de (Revista Gestão da Produção Operações e Sistemas, 2007)
Universities have strived to reflect the transformations taking place nowadays by assuming an entrepreneur modelfor managing the knowledge produced in them. In order to approach the subject, this study sought to comparethe opinion of research group leaders from a public Brazilian university with its institutional policy of scienceand technology and innovation. The adopted method was of an exploratory nature with quantitative variables.The data were collected by means of a structured questionnaire directed to the group leaders. The sample wasprobabilistic and the data analyzed by means of bivariate (correlation and crossbabs) and multivariate (clusters)statistical techniques. The results showed that despite a certain integration between the positioning of theresearch group leaders and the objective reflected in the policies for science, technology and innovation, theUniversity still faces a great challenge, which is to transform its potential into practical results.Keywords: Innovation; Technology transfer; Institutional policy; Research group leaders.